CONSTRUCCIÓN TERRITORIAL, VULNERABILIDAD SOCIAL Y CALIDAD AMBIENTAL EN EL EJIDO DE VILLA PEHUENIA, PROVINCIA DEL NEUQUÉN, ARGENTINA - Celia Torrens; Elsie M. Jurio (Boletín Geográfico)
The environmental situation of a region is linked to inherent changes and relations in the successive transformations that happened along the historical process of its territorial building. This process involves sustained social and economic relations on cultural patterns, political, institutional, and legal and policy dimensions and natural processes and relations of social groups with nature. Unlike other areas of the province, in Villa Pehuenia, located in Aluminé Department in the mountainous area of the Province of Neuquén, vulnerability and risk are not always related to situations of high levels of poverty and the exclusion of social groups. Territorial construction has been marked by the decisions and changes in the politics of the Provincial and National Government. In a territory where the natural and landscape resources are the key for defining development profile, this was directed at first to the primary activities (extensive livestock and forestry), and today, to tertiary activities related to tourist services. Consequently, the demographic and occupational dynamic is being transformed. Life in villages and rural areas undergoes gradual changes. Due to the growing and dynamic changes, it becomes essential to analyse the modes of appropriation of natural resources, considering a high degree of environmental sustainability and promoting the development of specific strategies and policies to anticipate potential negative impacts.